Relationship Between Knowledge and History of Low Birth Weight with the Incidence of Stunting Among Toddlers in Public Health Center - Purwati, Wilia; Sutarno, Maryati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: To determine the relationship between knowledge and historical records of low birth weight (LBW) and the prevalence of stunting in young children at the Cibadak Community Health Center in Lebak Regency. Method: The study used incidental sampling, involving women with toddlers at the Cibadak Community Health Center, to evaluate their health, using SPSS 22, chi square, and Spearman rank tests. Results: The results of the research show that knowledge and history of LBW in toddlers have a significant relationship. The p value from the chi square test on the history of LBW with stunting has a value of 0.000, as well as the p value in the Spearman rank test on the mother's knowledge variable regarding the incidence of stunting also has a value of 0.000. Conclusions: The study focuses on the link between awareness and medical history of low birth weight and stunting in toddlers, emphasizing the necessity of nutritional programs and attention from healthcare providers.